Short-latency prepulse inhibition of the trigeminal blink reflex - Shingaki, Megumi; Itoh, Yasushi; Borgil, Bayasgalan; Kida, Tetsuo; Inui, Koji (Frontiers in Neuroscience, 2024)
Prepulse inhibition (PPI) is a well-established phenomenon wherein a weak sensory stimulus attenuates the startle reflex triggered by a subsequent strong stimulus. Within the circuit, variations in target responses observed for PPI paradigms represent prepulse-induced excitability changes. However, little is known about the mechanism of PPI. Here, we focused on short-latency PPI of the trigeminal blink reflex R1 signal with an oligosynaptic reflex arc through the principal sensory trigeminal nucleus and the facial nucleus. As the facial nucleus is facilitatory to any input, R1 PPI is the phenomenon in the former nucleus. Considering that GABAergic modulation may be involved in PPI, this study investigated whether the PPI mechanism includes GABA-A equivalent inhibition, which peaks at approximately 30 ms in humans. In 12 healthy volunteers, the reflex was elicited by electrical stimulation of the supraorbital nerve, and recorded at the ipsilateral lower eyelid by accelerometer. Stimulus intensity was 1.5 times the R1 threshold for test stimulus and 0.9 times for the prepulse. The prepulse–test interval (PTI) was 5–150 ms. Results showed significant inhibition at 40-and 80–150-ms PTIs but not at 20-, 30-, 50-, 60-, and 70-ms PTIs, yielding two distinct inhibitions of different time scales. This corresponds well to the early and late components of inhibitory post synaptic potentials by GABA-A and GABA-B receptor activation. Thus, the data support the contribution of inhibitory post synaptic potentials elicited by the prepulse to the observed PPI. As inhibitory function-related diseases may impair the different inhibition components to varying degrees, methods deconvoluting each inhibitory component contribution are of clinical importance.